Pengaruh Aromaterapi Lavender Terhadap Tingkat Kecemasan Ibu Pre Operasi Sectio Caesarea - Sri Yuliani; Nurul Ainul Shifa; Rina Afrina (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Feelings of anxiety in pre-Section Caesarea mothers can cause unstable conditions that will disrupt the operation process itself, so appropriate ways are needed to overcome anxiety in mothers, one of which is lavender aromatherapy. This study aims to determine the effect of lavender aromatherapy on maternal anxiety levels before Caesarean section surgery. This type of research is pre-experimental with a one group pretest-posttest design. Respondents in this study were mothers pre-operatively with Sectio Caesarea in the Azra Hospital inpatient room, totaling 30 respondents using a non-probability sampling technique using consecutive sampling. Pre-test and post-test data were collected by filling in the Self Anxiety Rating-Scale (SAS) questionnaire. Research analysis was carried out in stages, namely univariate analysis and bivariate analysis using the Paired Sample T-Test. The results of the research showed that the average anxiety level of respondents before being given lavender aromatherapy was 55.7 and the average anxiety level of respondents after being given lavender aromatherapy was 37.6 and there was an effect of giving lavender aromatherapy on the anxiety level of mothers before Caesarean section surgery p value 0.001 (CI; 95% ). The conclusion of the research is that giving lavender aromatherapy can be a non-pharmacological therapy option to reduce anxiety levels in pre-caesarean section surgery patients..